The dynamics of referral hiring and racial inequality: Evidence from Brazil - Conrad Miller; Ian Schmutte (W.E. Upjohn Institute for Employment Research, 2021)
Economic theory predicts that intertemporal decisions depend critically on expectations about future outcomes. Using the universe of professional survey forecasts for the United States, we document the behavior of the entire term structure of expectations for output growth, inflation, and the policy rate. We show that a simple unobserved components model of the trend and cycle explains the joint behavior of both consensus measures of expectations and the observed disagreement among individual forecasters. Importantly, univariate models of each variable are outperformed by a multivariate model of the joint dynamics of these three variables, particularly for nominal interest rates. Consistent with the data, the model predicts a link between revisions in long-run expectations to short-term forecast errors. In structural models, learning about the long run has important empirical and theoretical implications for monetary and fiscal policy.We study how referral hiring contributes to racial inequality in firm-level labor demand over the firm's life cycle using data from Brazil. We consider a search model where referral networks are segregated, firms are more informed about the match quality of referred candidates, and some referrals are made by nonreferred employees. Consistent with the model, we find that firms are more likely to hire candidates and less likely to dismiss employees of the same race as the founder, but these differences diminish as firms' cumulative hires increase. Referral hiring helps to explain racial differences in dismissals, seniority, and employer size.
Keywords: D83; J15; J23; J42; J63; L25; 330; referral hiring; search model; match quality; racial differences; Brazil